Evaluation of pre-symptom activity of fungicides against Marssonina coronaria causing premature leaf fall in apple - J.N. SHARMA, ANIL KUMAR* and (Indian Phytopathology, 2015)
Fifteen fungicides were evaluated for their pre-symptom activities against Marssonina coronaria causing premature leaf fall in apple under polyhouse during 2009 and 2010. Mancozeb, captan, copper oxychloride, metiram, benomyl, carbendazim, thiophanate methyl, Shield, Kresoxim methyl, azoxystrobin, pyraclostrobin, hexaconazole, difenoconazole and tebuconazole were tested at 0.1, 0.2 and 0.3% concentration, whereas dodine at 0.05, 0.075 and 0.1%. Potted plants of apple cv Starking Delicious were inoculated with standardized conidial suspension (5 × 104 conidia ml-1) of M. coronaria and plants were treated 9 days after inoculation. Timing of application was based on incubation period (12 days) of M. coronaria on the test cultivar. Strobilurins (kresoxim methyl, pyraclostrobin and azoxystrobin) had strongest pre-symptom activity against the disease in polyhouse exhibited 70.99-91.08% control during both the years. These fungicides also had highest inhibitory effect on conidial production (4.25 × 104 conidia ml-1 - 5.54 × 104 conidia ml-1) and reduced lesion size (3-6 mm) produced on the treated leaves compared to other treatments. Captan was least effective against Marssonina blotch of apple among all the treatments exhibited 41.16-49.58% control during both the experimental years. Kresoxim methyl exhibited highest disease control (80.82-91.08%) among all the fungicides. It could be used for effective management of Marssonina blotch in apple.